Significance of multiple solutions on the dynamics of ethylene glycol conveying gold and copper nanoparticles on a shrinking surface - Naveed Khan, Muhammad; Alhowaity, Sawsan; Wang, Zhentao; Alqahtani, Aisha M.; Tag-eldin, Elsayed; Yassen, Mansour F. (Frontiers in Physics, 2022)
Hybrid nanofluids improve the thermal conductivity of the fluid. The nanoparticles Copper and gold with ethylene glycol as a base fluid are used here. The flow problem is described over a stretching/shrinking surface with the influence of Ohmic heating, non-linear radiation, and convectively heated surface. Furthermore, the magnetic field strength is applied perpendicular to the direction of flow. To control the fluid flow governing equations are numerically solved by using bvp4c a built-in approach in Matlab. For hybrid nanomaterials, the consequence of different physical parameters is discussed graphically and with tabular data. A comparison with previous findings reveals that the present ones are in good agreement. It is seen from the numerical values of the coefficient of skin friction that the physically stable branch declines over a certain range of shrinking parameters; nonetheless, for the unstable branch, the reverse pattern is discovered. The magnetic force diminishes the flow field and energy dispersion in the upper branch but improves it in the lower branch.